Prevalence of mastitis and their relations with risk factors in extensively managed sheep flocks (Indian Journal of Animal Production and Management, 2025)
Mastitis presents a significant challenge in sheep flocks, akin to its impact on high producing dairy cows. This condition not only reduces milk yield but also negatively  affects pre-weaning lamb growth, potentially increasing lamb mortality due to  starvation in meat-producing flocks. In India, particularly in Sabarkantha district,  data on the prevalence of clinical mastitis in extensively managed sheep flocks are  limited, partly due to the practice of not milking ewes, which leads to undetected cases.  This study aimed to assess the prevalence of clinical mastitis and its association with  various risk factors in Sabarkantha district of Gujarat, where sheep are traditionally  managed by the Bharvad community through grazing in both hilly and plain areas. A  total of 21 flocks from 12 villages were randomly selected, with 6 villages each from  plain and hilly regions involving 617 lactating ewes. Clinical mastitis was diagnosed  based on symptoms such as udder swelling and abnormal milk. Data on risk factors  including parity number, floor hygiene, treatment practices, and flock size were also  collected. Composite milk samples from affected ewes were analyzed for bacterial  culture and identification. The results showed that the overall prevalence of clinical  mastitis in ewes was 10.19±0.64%. Flocks size was found to be associated with  mastitis prevalence %, as it was higher i.e. 13.71% in larger flocks compare to small or  medium sized flocks may be attributed to poorer hygiene conditions particularly in  large flocks. Parity number and regional differences significantly impacted mastitis  prevalence, with higher prevalence in sheep with more parities and in plain regions  compared to hilly areas. Treatment practices were found to significantly affect mastitis  frequency, with a notable decrease in prevalence when treatment was administered.  Bacteriological analysis of 47 positive mastitis cases revealed Staphylococcus spp. as  the most common pathogen, followed by Streptococcus spp., E. coli, Pseudomonas  spp., and other Gram-negative bacteria. The study highlights the need for targeted  mastitis control strategies, considering factors such as parity number, regional  differences, and treatment practices, to effectively manage mastitis in grazing sheep  systems.
Keywords: Clinical Mastitis; Floor hygiene; Parity; Prevalence; Risk factors; Sheep flocks